(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
(Achieving health goals in provinces and the country, a strategy with detail specification on motive/development tools is proposed at various demographic levels. This elaborate strategy with necessary assignments, tasks, and activities will be supportive in organizing a specific and actionable approach for these tasks.